2022
DOI: 10.3390/rs14092084
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Photovoltaic Energy in China Based on Global Land High-Resolution Cloud Climatology

Abstract: As clean, renewable energy, photovoltaic (PV) energy can reduce the ozone-layer loss and climate deterioration caused by the use of traditional types of energy to generate electricity. At present, most PV energy products involve the influence of cloud cover on solar radiation. However, the resolution and precision of most cloud cover data are not fine enough to reflect the actual cloud distribution in local areas. This leads to incorrect distribution results of PV energy in areas with high-spatial-variability … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 71 publications
0
1
0
Order By: Relevance
“…In recent years, with in-depth research on the efficiency and stability of PV power generation systems, the impact of cloud cover on PV power has increasingly attracted the attention of scholars. A series of studies have shown that clouds directly alter the amount of radiation received by PV panels by blocking, reflecting, and scattering solar radiation, thus affecting the power output of PV power plants [64,65]. To more accurately predict and assess the impact of cloud cover on PV power, researchers have employed various methods for data collection and analysis.…”
Section: The Impact Of Cloud Cover On the Prediction Of Photovoltaic ...mentioning
confidence: 99%
“…In recent years, with in-depth research on the efficiency and stability of PV power generation systems, the impact of cloud cover on PV power has increasingly attracted the attention of scholars. A series of studies have shown that clouds directly alter the amount of radiation received by PV panels by blocking, reflecting, and scattering solar radiation, thus affecting the power output of PV power plants [64,65]. To more accurately predict and assess the impact of cloud cover on PV power, researchers have employed various methods for data collection and analysis.…”
Section: The Impact Of Cloud Cover On the Prediction Of Photovoltaic ...mentioning
confidence: 99%
“…Among various new energy industries, solar power generation is environmentally friendly, because it doesn't emit harmful greenhouse gases or toxic byproducts [1][2][3][4][5]. In addition, the global available solar energy resources are prosperous, especially in low latitudes [6]. With the advancement of technology, the cost of photovoltaic power generation is getting lower and lower.…”
Section: Introductionmentioning
confidence: 99%